DNA Methylation of PTGIS Enhances Hepatic Stellate Cells Activation and Liver Fibrogenesis - Pan, Xue-yin; Yang, Yang; Meng, Hong-wu; Li, Hai-di; Chen, Xin; Huang, Hui-min; Bu, Fang-tian; Yu, Hai-xia; Wang, Qin; Huang, Cheng; Meng, Xiao-ming; Li, Jun (Frontiers in Pharmacology, 2018)
Abstract The activation of hepatic stellate cells (HSCs) is a central event in the progression of liver fibrosis. Multiple studies proved that DNA methylation might accelerate HSCs activation. However, the specific pathogenesis of liver fibrosis remains not fully addressed. Our laboratory performed Genome methylation screening to find out the methylated gene in mice with liver fibrosis. The pilot experiments showed that the promoter of prostacyclin synthase (PTGIS) gene was hypermethylated in CCl4-induced liver fibrosis mouse model. Moreover, the down-regulated PTGIS expression can be restored by DNMTs-RNAi and 5-aza-2-deoxycytidine (5-azadC), an inhibitor of DNA methyltransferase (DNMTs). Methylation-specific PCR (MSP) showed that the methylation status of PTGIS in HSC-T6 cells cultures with TGF-β1 (10ng/mL) was elevated compared with control group. Chromatin immunoprecipitation (ChIP) assay indicated that PTGIS methylation was mainly induced by DNMT1 and DNMT3b. We further investigated the function of PTGIS in liver fibrosis by Recombinant Hepatic-adeno-associated virus (rAAV8)-PTGIS overexpression. The data indicated that overexpression of PTGIS in mouse liver accompanied by elevated apoptosis-related proteins expression in primary hepatic stellate cells. Conversely, PTGIS silencing mediated by RNAi enhanced the expression of α-SMA and COL1a1 in vitro. Those results illustrated that adding PTGIS expression inhibits the activation of HSCs and alleviates liver fibrosis. Therefore, our study unveils the role of PTGIS in HSCs activation, which may provide a possible explanation for CCl4-mediated liver fibrosis.